Disseminated coxsackievirus A6 affecting children with atopic dermatitis. (1st July 2015) - Lynch, M. D.; Sears, A.; Cookson, H.; Lew, T.; Laftah, Z.; Orrin, L.; Zuckerman, M.; Creamer, D.; Higgins, E.
Summary: Coxsackievirus A6 (CV‐A6) is an emerging pathogen that has in recent years been associated with atypical hand, foot and mouth disease. This manifests as a generalized papular or vesicular eruption, which may be associated with fever and systemic disturbance. We report a series of six children presenting to a single centre in the UK with disseminated CV‐A6 infection on a background of atopic dermatitis (AD). Our patients exhibited a widespread papular or vesicular eruption in association with exacerbation of AD. Several of our cases mimicked eczema herpeticum, but the extent was more generalized, and individual lesions were discrete rather than clustered and were less circumscribed in character. This series highlights that CV‐A6 infection may be encountered in the UK, and should be considered in the differential diagnosis of an acute exacerbation of AD, particularly in children.